1996
DOI: 10.1073/pnas.93.9.4345
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the RNA binding sites of iron regulatory proteins and potential target diversity.

Abstract: Posttranscriptional regulation of genes of mammalian iron metabolism is mediated by the interaction of iron regulatory proteins (IRPs) with RNA stem-loop sequence elements known as iron-responsive elements (IREs)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
115
1
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(124 citation statements)
references
References 38 publications
6
115
1
2
Order By: Relevance
“…Replacement of the consensus adenine with guanosine might alter the orientation of this stacking interaction, but such a change is unlikely to produce a large ⌬⌬G 25 (complex). Although SELEX experiments have confirmed the preference for adenosine at this site, one study found cytidine in several IRP-binding clones and guanosine in a single IRP2-specific sequence containing multiple nonconsensus nucleotides (23), whereas the other identified cytidine-and uridine-containing sequences (24). The tolerance of substitutions other than guanosine at this site suggests that this nucleobase may be involved in a stacking interaction with the IRP and that the large size of guanosine may disrupt this association under most conditions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Replacement of the consensus adenine with guanosine might alter the orientation of this stacking interaction, but such a change is unlikely to produce a large ⌬⌬G 25 (complex). Although SELEX experiments have confirmed the preference for adenosine at this site, one study found cytidine in several IRP-binding clones and guanosine in a single IRP2-specific sequence containing multiple nonconsensus nucleotides (23), whereas the other identified cytidine-and uridine-containing sequences (24). The tolerance of substitutions other than guanosine at this site suggests that this nucleobase may be involved in a stacking interaction with the IRP and that the large size of guanosine may disrupt this association under most conditions.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that with every mutation, except Pavia 2, the affinity for IRP1 was more affected than for IRP2. Studies of nonconsensus IRP-binding sequences have shown that, in general, IRP2 has a greater tolerance for mutations within the hexanucleotide loop of the IRE (23,24). Additionally, the IRE binding capacity of IRP2 is much less affected by mutagenesis of individual arginines within the putative IRE-binding site (23).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, when iron is abundant, a conformational change in IRP-1 prevents its interaction with the IREs and degradation of IRP-2 is increased. 5 In the absence of the negative regulatory influence of the IRPs, the (mRNA)FTL and (mRNA)FTH are translated constitutively and apoferritin is synthesised. 3 Hereditary hyperferritinaemia cataract syndrome (HHCS; OMIM 600886) is an autosomal dominant disorder of ferritin synthesis characterised by early onset cataracts and increased serum concentration of L-ferritin.…”
Section: Introductionmentioning
confidence: 99%